The connection between unpredictable maternal signaling in caregiving behaviour and child’s overweight at the age of two years - Saharinen, Lotta (My University, 2021)
Children’s overweight is a progressive issue worldwide. In Finland, 23% of two-year-old children are overweight or obese. Overweight may lead to several other illnesses and diseases, as well as a shorter life expectancy. For example, maternal smoking and overweight, child’s birth weight and nutrition and feeding patterns might influence child’s weight gaining. Also, a supportive environment is known to be positively connected to child’s normal weight through good care taking of the child early in life whereas unfavorable caregiving might be risky for normal weight development. Recent studies have shown that unpredictable maternal signals are one aspect in caregiving behavior that may influence child’s development in neurocognition and self-regulation. However, unpredictable maternal caregiving signals have not been studied in the context of child weight gain. The hypothesis was that more unpredictable maternal signals in caregiving might affect child’s weight gain leading to overweight. The connection between unpredictable maternal signaling in caregiving behaviour and child’s overweight at the age of two years was studied using the novel method of entropy rate (ER). The data was collected from the FinnBrain Birth Cohort study. The ER was assessed from 133 mother-child-dyads during a 10-minute mother-child playing episode at the child age of 8 months. Maternal infant-directed sensory signals (visual, auditory, tactile) were counted from the video recordings, and ER was calculated based on the predictability of the transitions between the signals. The higher the ER, the more unpredictable the maternal sensory signals are. The weight data of the two-year-old was assessed from the parental questionnaires (n = 1244) and was split into two groups: normal/underweight (group 1) and overweight/obese (group 2). The final sample included 97 mother-child-dyads overlapping data of ER and weight data at the age of two years. The study was the first of its kind exploring relationship between predictability of maternal signals in caregiving behaviour and early childhood obesity. As a result, unpredictable maternal signals did not associate significantly with child overweight. Despite the null findings regarding to our hypothesis, there were some clues about connection between underweight and high ER indicating the opposite of our hypothesis. The results are not entirely reliable because of a modest sample size. Also, ER being a novel method in caregiving behaviour, further studies are required.

Lasten ylipaino on maailmanlaajuisesti lisääntyvä ongelma. Kaksivuotiaista suomalaisista lapsista noin 23 % on ylipainoisia tai lihavia. Ylipaino voi johtaa useisiin muihin tauteihin ja lyhyempään elinajanodotteeseen. Lapsen painoon vaikuttaa esimerkiksi äidin raskausajan tupakointi ja ylipaino, lapsen syntymäpaino, ravitsemus sekä syöttämistavat. Myös kannustavan ympäristön tiedetään olevan positiivisesti yhteydessä lapsen normaaliin painoon varhaislapsuuden hyvän huolenpidon myötä, kun taas epäsuotuisa hoivaaminen saattaa olla haitaksi normaalille painonkehitykselle. Viimeaikaisissa tutkimuksissa on todettu, että äidin ennustamattomat hoivasignaalit vaikuttavat osaltaan lapsen neurokognitiiviseen kehitykseen ja itsesäätelyyn. Äidin hoivasignaalien vaikutusta lapsen painonnousuun ei ole kuitenkaan tutkittu. Näiden tietojen pohjalta hypoteesimme on, että äidin ennustamattomat hoivasignaalit saattavat olla yhteydessä lapsen ylipainoon. Tässä tutkimuksessa tutkittiin äidin hoivakäyttäytymisen ennustettavuuden yhteyttä jälkikasvun liialliseen painonnousuun kahden vuoden iässä käyttämällä uutta määrettä, entropiaa (entropy rate, ER). Data kerättiin FinnBrain-syntymäkohorttitutkimuksesta. Entropia laskettiin 133 äiti–lapsiparilta äidin ja lapsen välisestä 10 minuutin leikkihetkestä lapsen ollessa 8 kuukauden ikäinen. Videosta laskettiin sensoriset (näkö-, kuulo- ja kosketus-) signaalit ja entropia-arvo saatiin näiden signaalien siirtymien todennäköisyyksistä. Mitä suurempi entropia on, sitä ennustamattomampia äidin hoivasignaalit ovat. Lasten painodata kahden vuoden iässä kerättiin vanhempien kyselylomakkeista (n = 1244) ja jaettiin kahteen ryhmään: normaali- ja alipainoiset (ryhmä 1) sekä ylipainoiset ja lihavat (ryhmä 2). Tutkimukseen sisällytettiin lopulta 97 äiti–lapsiparia, joista oli sekä paino- että entropiadata. Tutkimus oli ensimmäinen laatuaan selvittämässä äidin hoivakäyttäytymisen ennustettavuuden yhteyttä ylipainoon. Äidin ennustamattomilla hoivasignaaleilla ei todettu merkitsevää yhteyttä lapsen ylipainoon. Vaikka merkitseviä tuloksia ei saatu, viitteitä alipainon yhteydestä huonoon ennustettavuuteen (suureen entropiaan) oli, mikä tarkoittaisi päinvastaista tulosta hypoteesiin nähden. Tuloksia ei voi todeta täysin luotettaviksi liian pienen ryhmäkoon vuoksi. Lisäksi entropia uutena hoivakäyttäytymisen mittarina tarvitsee lisätutkimuksia.
Keywords: early-life, mother-child interaction, obesity, overweight, two-year-old